Contribution of CYP2D6 Functional Activity to Oxycodone Efficacy in Pain Management: Genetic Polymorphisms, Phenoconversion, and Tissue-Selective Metabolism - Malavika Deodhar; Jacques Turgeon; Veronique Michaud (MDPI AG, 2021)
Oxycodone is a widely used opioid for the management of chronic pain. Analgesic effects observed following the administration of oxycodone are mediated mostly by agonistic effects on the μ-opioid receptor. Wide inter-subject variability observed in oxycodone efficacy could be explained by polymorphisms in the gene coding for the μ-opioid receptor (OPRM1). In humans, oxycodone is converted into several metabolites, particularly into oxymorphone, an active metabolite with potent μ-opioid receptor agonist activity. The CYP2D6 enzyme is principally responsible for the conversion of oxycodone to oxymorphone. The CYP2D6 gene is highly polymorphic with encoded protein activities, ranging from non-functioning to high-functioning enzymes. Several pharmacogenetic studies have shown the importance of CYP2D6-mediated conversion of oxycodone to oxymorphone for analgesic efficacy. Pharmacogenetic testing could optimize oxycodone therapy and help achieve adequate pain control, avoiding harmful side effects. However, the most recent Clinical Pharmacogenetics Implementation Consortium guidelines fell short of recommending pharmacogenomic testing for oxycodone treatment. In this review, we (1) analyze pharmacogenomic and drug-interaction studies to delineate the association between CYP2D6 activity and oxycodone efficacy, (2) review evidence from CYP3A4 drug-interaction studies to untangle the nature of oxycodone metabolism and its efficacy, (3) report on the current knowledge linking the efficacy of oxycodone to OPRM1 variants, and (4) discuss the potential role of CYP2D6 brain expression on the local formation of oxymorphone. In conclusion, we opine that pharmacogenetic testing, especially for CYP2D6 with considerations of phenoconversion due to concomitant drug administration, should be appraised to improve oxycodone efficacy.